Ocena atrakcyjności inwestycyjnej krajów Europy Środkowo-Wschodniej - Stawicka, Magdalena (Rating of Investment Attractiveness in Central and Eastern European Countries, 2006)
The author picks over the rating test of investment attractiveness in nineteen countries of Central and Eastern Europe on a basis of chosen macroeconomic measures. The author uses this factor о carry out an analysis. Then she classifies countries in order of their attractiveness for foreign investors. Moreover the Author uses the analysis to distinguish between the most and the least attractive regions in Central and Eastern European countries. The results of probes were introduced in form of dendrogram, and the results were confirmed by using method A-means.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 130-144